2023
DOI: 10.22541/au.167345470.07189938/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tropical butterflies use thermal buffering and thermal tolerance as alternative strategies to cope with temperature increase

Abstract: Climate change poses a severe threat to many taxa, with increased mean temperatures and frequency of extreme weather events predicted. Insects respond to non-optimal temperatures using behaviours or local microclimates to thermoregulate (thermal buffering ability), or through physiological tolerance. We studied the thermal buffering ability and thermal tolerance of a community of 54 butterfly species in Panama. Thermal buffering ability and tolerance were influenced by family, size, and colour, with Pieridae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 44 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…However, there is a possibility that strong thermal buffering ability may inhibit adaptation to tolerate higher temperatures, as individuals would rarely be exposed to selection to evolve mechanisms to cope with non‐optimal temperatures (Muñoz, 2022). For example, a recent study on tropical adult butterflies has shown that species with a weaker buffering ability also had lower thermal tolerance (Ashe‐Jepson et al., 2023). This theory, dubbed the ‘Bogert effect’ (Huey et al., 2003), may mean that species with strong buffering abilities may initially be less impacted by changing temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is a possibility that strong thermal buffering ability may inhibit adaptation to tolerate higher temperatures, as individuals would rarely be exposed to selection to evolve mechanisms to cope with non‐optimal temperatures (Muñoz, 2022). For example, a recent study on tropical adult butterflies has shown that species with a weaker buffering ability also had lower thermal tolerance (Ashe‐Jepson et al., 2023). This theory, dubbed the ‘Bogert effect’ (Huey et al., 2003), may mean that species with strong buffering abilities may initially be less impacted by changing temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, should microclimates be lost or an extreme weather event were to occur whereby temperatures rise or fall outside tolerable ranges (such as during a heatwave), species with strong buffering abilities could have a reduced thermal tolerance compared to species with weak buffering abilities, and may be disproportionately affected. This implies that most species may be vulnerable to climate change; however, further study is needed to determine whether thermal buffering ability interacts with thermal tolerance in Lepidoptera larvae (Ashe‐Jepson et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations